DA PAISAGEM VINÍCOLA PARA A FESTA: TURISTAS E ANFITRIÕES NA FESTA DO VINHO DA MADEIRA - Marujo, Noémi (2017)
The landscapes wineries express the culture of a people related to the vineyard and wine. They serve as a symbol of cultural identity that allows the identification of people with the place. The wineries landscapes, in some cases, are associated with wine festivals that seek to (re) interpret the symbolic elements of social existence of a community. Wine festivals can be a valued element of the encounter between tourists and hosts. This paper aims to identify ways of encounter between tourists and hosts in rural area of the Madeira Wine Festival. To achieve the goal we chose the direct observation.